Penerapan Strategi Marketing Mix 4P pada Pelaku Usaha UMKM Es Teh Jumbo - Aditya Ramadhan; Andika; Vira Sasmita; zainarti (MERDEKA : Jurnal Ilmiah Multidisiplin, 2026)
This study aims to provide an in-depth analysis of the implementation of the 4P Marketing Mix strategy within Es Teh Jumbo, an MSME beverage business that has grown rapidly as a popular and affordable contemporary drink. The research focuses on how the business manages product quality, determines competitive pricing, selects strategic locations, and carries out promotional activities both directly and through digital platforms. A qualitative descriptive approach was used, employing data collection techniques such as field observation, interviews with business owners and consumers, and supportin documentationn.  The findings reveal that the product strategy emphasizes offering large-sized tea beverages with a variety of flavors  that cater to consumer preferences. The pricing strategy is designed to remain accessible for students and the general public, making the product more appealing. The business is strategically located in crowded areas that facilitate easy customer access. Meanwhile, promotional efforts rely mainly on social media and word-of-mouth, which indicates that the promotional aspect is not yet fully optimal. Overall, the study concludes that the application of the 4P Marketing Mix contributes positively to increasing consumer interest and sustaining the business growth of Es Teh Jumbo, although further improvements are needed, especially in enhancing digital promotional strategies.